Masyarakat, Desa dan Madrasah (Studi Tentang Pandangan Masyarakat terhadap Madrasah di Desa Telaga Biru Tanjungbumi Bangkalan) - Afandi, Afandi; Muksin, Muksin (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
The village community in the implementation of education is greatly assisted by the existence of Islamic boarding schools, especially in remote areas. Even distribution of education in remote areas is still a problem faced by the government in providing education. The community is greatly helped by the existence of Islamic boarding schools in education and religious and other social activities. This research is a descriptive qualitative research which aims to explore the relationship between the village community and the madrasah. The research method used in this study is a descriptive qualitative method, namely describing field findings without any intervention or effort to make certain changes to the object of research. The result of this research is that with the diversity of opinions or views expressed by respondents with different backgrounds, there are actually no significant differences of opinion between respondents. In short, the public's view of the madrasa in Telaga Biru Village, Kec. Tanjung Bumi Kab. Bangkalan cannot be dichotomized based on the respondent's background. This is because the respondents' views in one particular aspect are different, but they have similarities in other aspects.